"Idiots, infants, and the insane": mental illness and legal incompetence. Issue 2 (28th January 2005) - Szasz, T
Abstract : Prior to the second world war, most persons confined in insane asylums were regarded as legally incompetent and had guardians appointed for them. Today, most persons confined in mental hospitals (or treated involuntarily, committed to outpatient treatment) are, in law, competent; nevertheless, in fact, they are treated as if they were incompetent. Should the goal of mental health policy be providing better psychiatric services to more and more people, or the reduction and ultimate elimination of the number of persons in the population treated as mentally ill?